Black phosphorous nanosheet: A novel immune-potentiating nanoadjuvant for near-infrared-improved immunotherapy. (June 2021) - Li, Wen-Hao; Wu, Jun-Jun; Wu, Lie; Zhang, Bo-Dou; Hu, Hong-Guo; Zhao, Lang; Li, Zhi-Bin; Yu, Xue-Feng; Li, Yan-Mei
Abstract: Intrinsic immune behaviors of nanomaterials and immune systems promote research on their adjuvanticity and the design of next generation nanovaccine-based immunotherapies. Herein, we report a promising multifunctional nanoadjuvant by exploring the immune-potentiating effects of black phosphorus nanosheets (BPs) in vitro and in vivo . The facile coating of BPs with phenylalanine-lysine-phenylalanine (FKF) tripeptide-modified antigen epitopes (FKF-OVAp@BP) enables the generation of a minimalized nanovaccine by integrating high loading capacity, efficient drug delivery, comprehensive dendritic cell (DC) activation, and biocompatibility for cancer immunotherapy. Systemic immunization elicits potent antitumor cellular immunity and significantly augments checkpoint blockade (CPB) against melanoma in a mouse model. Furthermore, near-infrared (NIR) photothermal effects of BPs create an immune-favorable microenvironment for improved local immunization. This study offers new insight into the integration of immunoactivity and photothermal effects for enhanced cancer immunotherapy by using a nanoadjuvant and thus potentially advances the design and application of multifunctional adjuvant materials for cancer nanotreatment.